Theoretical study of the structural and energetic properties of the ethane activation by single neutral and charged metal oxides - Arrieta, Federico; Figueredo, Benjamín; Rosa Brussin, Marcos; Hinchliffe, Alan; Soscún, Humberto (Ciencia, 2011)
We present a theoretical study of the structural and energetic properties of the chemical activation of ethane (C2,H6) in gas phase, by direct interaction with metal oxides such as [MO]0, (M = Ti, Cr, Fe, Ni, Zn) and [MO]+, (M = V, Mn, Co, Cu, Ga). The calculations were performed with the B3LYP method and the 6-31+G(d,p) basis set. The geometries were fully optimized and the results show that the M-O bonding energies of the charged species are lower that those of the neutral ones. For each series of the metal oxides, the bonding energies increase with the atomic number of M. The interaction between C2H6 and the MO, restricted to Cs symmetry, leads to the formation of different [C2H6,-MO] molecular complexes structures. which can be associated to the d electronic configuration of M. The structure of these complexes gives information about the preferences for the chemical activation of C2H6 by effect of the MO, that can be summarized as: a) Ti(II)(d2), V(III) (d2) and Fe(II)(d6) produce [C2H6-M] adsorption complexes only; b) Cr(II)(d4), produce the alkyl and the hydride groups coordinated to the metal by ï³ bonds (CH3CH2-Cr(O)-H); c) Mn(III)(d4) and Co(III)(d6) activate the ethane towards the formation of ethanol adsorbed on the metal (CH3CH2OH-M); d) Ni(II) (d8) and Cu(III)(d8) activate ethane to the formation of alkyl and the hydroxyl groups coordinated by a bonds to the metal [(CH3CH2-M-OH), e] Zn(II)(d10) and Ga(III)(d10) give the formation of ethene and water adsorbed to the metal (CH2CH2-M-H2O). The charged oxide species give higher reaction energies than the neutral ones.